Sharia Stock Investment On The Indonesia Stock Exchange In The Perspective Of Sharia Economic Law - Laila, Ahrina; Harianto, Harianto; Azwari, Peny Cahaya (Jurnal Fokus Manajemen, 2025)
This type of research uses qualitative research, then the type of research is a literature study (library research), which is a study carried out using journal literature, books, previous research results, notes on research report results. The data collection technique in this study uses book journal literature, while the analysis used is descriptive analysis. The results of the study show that investment in sharia stocks on the IDX has in principle complied with sharia provisions, but there is still a need to strengthen sharia literacy and stricter supervision.